2014
DOI: 10.6023/a13111179
|View full text |Cite
|
Sign up to set email alerts
|

SCFT Study of Microphase Separation in Mixed Polymer Brushes Grafted on Cylindrical Surface

Abstract: We report on microphase separation behaviors of mixed polymer brushes grafted onto an infinitely long cylindrical rod by performing polymer self-consistent field theory (SCFT) calculation with "masking" technique. The "masking" technique is especially suitable to deal with systems of confined polymers grafted onto curved surfaces. We have developed a method to solve the morphology of block copolymers confined into complicated topographic surfaces with SCFT. In this paper, this unique technique is extended to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Fortunately, more efficient two-dimensional (2D) calculations are helpful to deal with this problem. Our previous work 19 showed that the basic physical rule governing the microphase behavior of mixed polymer-grafted particles is essentially the same in 2D. In this case, the balance between the A/B interface interaction and the chain stretching will result in rippled phases with optimal domain numbers for the isolated symmetric binary hairy particle.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Fortunately, more efficient two-dimensional (2D) calculations are helpful to deal with this problem. Our previous work 19 showed that the basic physical rule governing the microphase behavior of mixed polymer-grafted particles is essentially the same in 2D. In this case, the balance between the A/B interface interaction and the chain stretching will result in rippled phases with optimal domain numbers for the isolated symmetric binary hairy particle.…”
mentioning
confidence: 96%
“…Their results suggest a new method to manipulate nanoparticles with precisely controlled numbers and locations of active sites. Recently, by incorporating the “masking” technique into the SCFT, we systematically investigated the morphology of isolated binary hairy nanoparticles. Our method to solve the SCFT equations on a spherical surface in a simple Cartesian coordinate system utilizes the efficient and highly accurate pseudospectral method . Meanwhile, Zhao and Zhu carried out a series of experiments to study the microphase structures of mixed poly­( tert -butyl acrylate) (P t BA)/polystyrene (PS) brushes grafted on a silica particle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the difference of the free energy between the two phases has a strong dependence on solvent entropy, and hence they predicted that both the parallel ripple and ring phases are possible to be observed in experiments. Subsequently, they also investigated the microphase separation of mixed brushes on an infinitely long cylinder . Without the spatial constraint of the two semi‐spherical caps, regular parallel ripple phase and ring phase can be obtained more easily.…”
Section: Binary Polymer Brushes On Curved Surfaces: “Multifaceted” Hamentioning
confidence: 99%
“…17 However, it was found that the free energy of the system is mainly determined by the entropy of the solvent, which means that a slight change of the solvent selectivity could reverse the relative stability of perpendicular and parallel ripple structures. 18 In this paper, to simplify the system, we removed the solvent, and investigated a brush consisting of two chemically incompatible homopolymers graed onto cylindrical surfaces (in reality this corresponded to mixed brushes in contact with a neutral polymer melt composed of much longer chains, ensuring a dry brush condition). We assumed that the chain end segments were xed by covalent connection to the graing site, i.e., the system could only undergo microphase separation.…”
Section: Introductionmentioning
confidence: 99%